2016
DOI: 10.3233/jad-160581
|View full text |Cite
|
Sign up to set email alerts
|

Potentially Inappropriate Medication in Community-Dwelling Primary Care Patients who were Screened Positive for Dementia

Abstract: Background: Potentially inappropriate medication (PIM) in older people is a risk factor for adverse drug effects. This risk is even higher in older people with dementia (PWD).Objective: Our study aimed to determine (1) the prevalence of PIM among primary care patients who were screened positive for dementia and (2) the sociodemographic and clinical variables associated with the use of PIM.Methods: DelpHi-MV (Dementia: life- and person-centered help in Mecklenburg–Western Pomerania) is a general practitioner-ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
30
0
5

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 47 publications
4
30
0
5
Order By: Relevance
“…Other studies have identified high levels of polypharmacy with potentially inappropriate prescribing in people with dementia ranging from 22% to 81.5% of participants . We found that medication review focussing on simplifying the regimen might be helpful, particularly if delivered in the home environment.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Other studies have identified high levels of polypharmacy with potentially inappropriate prescribing in people with dementia ranging from 22% to 81.5% of participants . We found that medication review focussing on simplifying the regimen might be helpful, particularly if delivered in the home environment.…”
Section: Discussionmentioning
confidence: 79%
“…In the UK, 800 000 people live with dementia – this figure is expected to double by 2040 reflecting global predictions . The presence of dementia potentially increases the likelihood of the presence for risk factors for adverse drug reactions such as lack of pharmacy input, drug interactions, comorbidity and polypharmacy, amongst others . The cognitive impairment characteristic of dementia may result in a lack of capacity to safely self‐administer medication .…”
Section: Introductionmentioning
confidence: 99%
“…[54][55][56] The results of the logistic regression analysis showed that the likelihood of PIMs increased with the number of medications prescribed, which is akin to the findings of the research in older people with dementia in care homes in the United Kingdom. 41 The study by Wucherer et al in community-dwelling primary care patients screened positive for dementia, 57 and the research conducted in Sweden used the EU(7)-PIM list to evaluate the prevalence of PIMs in older people with cognitive impairment. 52 A study performed in the United Kingdom, utilizing the primary care database of anonymised electronic health records from general practice, witnessed that patients more than 65 years of age diagnosed with dementia, and taking multiple medications, were more likely to be prescribed antipsychotics.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the increased risk of adverse events and limited evidence for the efficacy of BZDR, earlier studies reported a relatively high prescription rate in dementia patients [9][10][11]. Though, the majority of earlier evaluations were based on claims data of health insurance companies or considered dementia patients in certain healthcare settings (e. g., only nursing home inhabitants or community-dwelling patients) [9][10][11][12][13][14][15]. In contrast, our study includes patients with AD across all severity stages of dementia and from different residential sites.…”
Section: Introductionmentioning
confidence: 99%